Core–shell fibremats comprising a poly(AM/DAAM)/ADH nanofibre core and nylon6 shell layer are an attractive immobilization platform for constructing immobilised enzymes. Issue 54 (7th December 2022) - Ishiguro, Taira; Obata, Akiko; Nagata, Kenji; Kasuga, Toshihiro; Mizuno, Toshihisa
Abstract : Core–shell fibremats, comprising poly(AM/DAAM)/ADH core-nanofibres and hydrophobic shell layers, are a new class of attractive platform for constructing various immobilised enzymes. Abstract : Core–shell fibremats, comprising poly(acrylamide)- co -poly(diacetone–acrylamide)/adipic dihydrazide [poly(AM/DAAM)/ADH] core-nanofibres and hydrophobic polymer shell layers, are a new class of platforms for constructing various immobilised enzymes. In this study, to elucidate the impacts of the shell-layer material on fibremat properties and enzymatic activities, we synthesised core–shell fibremats with shell layers comprising nylon6 or acetyl cellulose (AcCel) instead of poly(ε-caprolactone) (PCL), as in our previous study. Transmission and scanning electron microscopy images revealed that the lactase-encapsulated poly(AM/DAAM)/ADH-nylon6 and -AcCel fibremats were both constructed like the poly(AM/DAAM)/ADH-PCL one. Leakage measurements of the beforehand loaded molecules inside the core-nanofibres revealed that both fibremats exhibited efficient permeability for low-molecular-weight molecules and stable retention of enzyme molecules inside the core-nanofibres. Meanwhile, the fibremats' mechanical properties considerably depended on the choice of shell-layer material. The thermal analyses of the lactase-encapsulated fibremats revealed residual water inside the core nanofibres. The core–shell fibremats fabricated with a nylon6 or PCL shell exhibited excellent enzymatic activities (102 and 114%, respectively, compared to that of free lactase), superior to that of the same amount of free enzyme in a buffer. Furthermore, both core–shell fibremats retained over 95% of their initial enzymatic activities, even after they were re-used 10 times.